Pengaruh Reward Dan Kepuasan Kerja Terhadap Motivasi Karyawan Pada PTPN IV Afdeling IV Kebun Pabatu - Suci Etri Jayanti S.; Ayu Zurlaini Damanik; Dea Paramita; Roma Syafarela Harahap (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
The purpose of this study is to analyze and test the Influence of Reward and Job Satisfaction on Employee Motivation at PTPN IV Afdeling IV Kebun Pabatu. This study uses a quantitative approach. The population in this study were all employees in Afdeling IV Kebun Pabatu, namely 39 employees. The sampling used was the Total Sampling technique. The data source in this study came from primary data, namely from the results of questionnaires filled out directly by respondents and Secondary Data, namely data obtained from other people or through documents. Hypothesis testing in this study Multiple Linear Regression on the SPSS version 25.00 application and analyzed using multiple linear regression techniques. The results of this study indicate that the first hypothesis is accepted, meaning that the Reward variable (X1)does not affect employee Motivation variable (Y). The results of the second hypothesis are accepted, meaning that the Job Satisfaction variable (X2) affects the Employee Motivation variable (Y). Based on the results of the analysis of the third hypothesis, it can be concluded that hypotheses 1 and 2 are accepted, meaning that the Reward variable (X1), Job Satisfaction (X2) simultaneously affect the Employee Motivation variable (Y).